Examining the Competences of Prospective Mathematics Teachers at Some State Islamic Universities in Sumatra - Eliza, Rivdya; Utami, Nita Putri; Wahid, Rahmatul (Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Kerinci, 2023)
Prospective teachers face complex 21st-century challenges. Therefore, prospective mathematics teachers must master several competencies to support students in acquiring and applying knowledge, collaborating with others, and developing as individuals. The purpose of this study was to measure the pedagogical, social, professional, and personality competencies of mathematics education students at the state Islamic universities in Central Sumatra region. This study used a questionnaire on the pedagogical, social, professional, and personality competencies of prospective teachers filled out by 211 students as respondents from 5 state Islamic universities. The findings of the study indicate that mathematics education students at these universities have good pedagogical and social competencies, including lesson planning, assessment, communication, and collaboration, along with solid professional competencies in subject knowledge and material development. While their personality competencies are considered very good because of their ethical behavior and strong work ethic. The universities should still improve 21st-century competencies of students in the curriculum through innovative teaching, internships, social engagement, emotional intelligence workshops, and practical training to improve their competencies and readiness for effective classroom engagement. Further research can assess its effectiveness.